Enhanced white matter fiber tract of the cortical visual system in visual artists: implications for creativity - Hong, Tzu-Yi; Yang, Ching-Ju; Cheng, Li-Kai; Li, Wei-Chi; Tseng, Wen-Yih Isaac; Yeh, Tzu-Chen; Yu, Hsin-Yen; Chen, Li-Fen; Hsieh, Jen-Chuen (Frontiers in Neuroscience, 2023)
This study aimed to examine the white matter characteristics of visual artists (VAs) in terms of visual creativity and the structural connectivity within the cortical visual system.Diffusion spectrum imaging was utilized to examine the changes in white matter within the cortical visual system of a group of VAs (n=25) in comparison to a group of healthy controls matched for age and education (n=24). To assess the integrity of white matter and its relationship with visual creativity, we conducted a comprehensive analysis using region-based and track-specific tractographic examinations.Our study uncovered that VAs demonstrated increased normalized quantitative anisotropy in specific brain regions, including the right inferior temporal gyrus and right lateral occipital gyrus, along with the corresponding white matter fiber tracts connecting these regions. These enhancements within the cortical visual system were also found to be correlated with measures of visual creativity obtained through psychological assessments.The noted enhancement in the white matter within the cortical visual system of VAs, along with its association with visual creativity, is consistent with earlier research demonstrating heightened functional connectivity in the same system among VAs. Our study's findings suggest a link between the visual creativity of VAs and structural alterations within the brain's visual system.